Recruitment of a SAP18-HDAC1 complex into HIV-1 virions and its requirement for viral replication. - Masha Sorin; Jennifer Cano; Supratik Das; Sheeba Mathew; Xuhong Wu; Kelvin P Davies; Xuanling Shi; S-W Grace Cheng; David Ott; Ganjam V Kalpana (PLoS Pathogens, 2009)
HIV-1 integrase (IN) is a virally encoded protein required for integration of viral cDNA into host chromosomes. INI1/hSNF5 is a component of the SWI/SNF complex that interacts with HIV-1 IN, is selectively incorporated into HIV-1 (but not other retroviral) virions, and modulates multiple steps, including particle production and infectivity. To gain further insight into the role of INI1 in HIV-1 replication, we screened for INI1-interacting proteins using the yeast two-hybrid system. We found that SAP18 (Sin3a associated protein 18 kD), a component of the Sin3a-HDAC1 complex, directly binds to INI1 in yeast, in vitro and in vivo. Interestingly, we found that IN also binds to SAP18 in vitro and in vivo. SAP18 and components of a Sin3A-HDAC1 complex were specifically incorporated into HIV-1 (but not SIV and HTLV-1) virions in an HIV-1 IN-dependent manner. Using a fluorescence-based assay, we found that HIV-1 (but not SIV) virion preparations harbour significant deacetylase activity, indicating the specific recruitment of catalytically active HDAC into the virions. To determine the requirement of virion-associated HDAC1 to HIV-1 replication, an inactive, transdominant negative mutant of HDAC1 (HDAC1(H141A)) was utilized. Incorporation of HDAC1(H141A) decreased the virion-associated histone deacetylase activity. Furthermore, incorporation of HDAC1(H141A) decreased the infectivity of HIV-1 (but not SIV) virions. The block in infectivity due to virion-associated HDAC1(H141A) occurred specifically at the early reverse transcription stage, while entry of the virions was unaffected. RNA-interference mediated knock-down of HDAC1 in producer cells resulted in decreased virion-associated HDAC1 activity and a reduction in infectivity of these virions. These studies indicate that HIV-1 IN and INI1/hSNF5 bind SAP18 and selectively recruit components of Sin3a-HDAC1 complex into HIV-1 virions. Furthermore, HIV-1 virion-associated HDAC1 is required for efficient early post-entry events, indicating a novel role for HDAC1 during HIV-1 replication.